A Multiple Piccolino-RIBEYE Interaction Supports Plate-Shaped Synaptic Ribbons in Retinal Neurons - Müller, Tanja; Gierke, Kaspar; Joachimsthaler, Anneka; Sticht, Heinrich; Izsvak, Zsuzsanna; Hamra, F. Kent; Fejtová, Anna; Ackermann, Frauke; Garner, Craig C.; Kremers, Jan; Brandstätter, Johann Helmut; Regus-Leidig, Hanna (Journal of Neuroscience, 2019)
Active zones at chemical synapses are highly specialized sites for the regulated release of neurotransmitters. Despite a high degree of active zone protein conservation in vertebrates, every type of chemical synapse expresses a given set of protein isoforms and splice variants adapted to the demands on neurotransmitter release. So far, we know little about how specific active zone proteins contribute to the structural and functional diversity of active zones. In this study, we explored the nanodomain organization of ribbon-type active zones by addressing the significance of Piccolino, the ribbon synapse-specific splice variant of Piccolo, for shaping the ribbon structure. We followed up on previous results, which indicated that rod photoreceptor synaptic ribbons lose their structural integrity in a knockdown of Piccolino. Here, we demonstrate an interaction between Piccolino and the major ribbon component RIBEYE that supports plate-shaped synaptic ribbons in retinal neurons. In a detailed ultrastructural analysis of three different types of retinal ribbon synapses in Piccolo/Piccolino-deficient male and female rats, we show that the absence of Piccolino destabilizes the superstructure of plate-shaped synaptic ribbons, although with variable manifestation in the cell types examined. Our analysis illustrates how the expression of a specific active zone protein splice variant (e.g., Piccolino) contributes to structural diversity of vertebrate active zones.
CRIS-Team WoS Importer:2019-04-12

Analysis of RIM Expression and Function at Mouse Photoreceptor Ribbon Synapses - Löhner, Martina; Babai, Norbert; Müller, Tanja; Gierke, Kaspar; Atorf, Jenny; Joachimsthaler, Anneka; Peukert, Angela; Martens, Henrik; Feigenspan, Andreas; Kremers, Jan; Schoch, Susanne; Brandstätter, Johann Helmut; et al. (The Journal of Neuroscience, 2017)
RAB3A-interacting molecule (RIM) proteins are important regulators of transmitter release from active zones. At conventional chemical synapses, RIMs contribute substantially to vesicle priming and docking and their loss reduces the readily releasable pool of synaptic vesicles by up to 75%. The priming function of RIMs is mediated via the formation of a tripartite complex with Munc13 and RAB3A, which brings synaptic vesicles in close proximity to Ca(2+) channels and the fusion site and activates Munc13. We reported previously that, at mouse photoreceptor ribbon synapses, vesicle priming is Munc13 independent. In this study, we examined RIM expression, distribution, and function at male and female mouse photoreceptor ribbon synapses. We provide evidence that RIM1? and RIM1? are highly likely absent from mouse photoreceptors and that RIM2? is the major large RIM isoform present at photoreceptor ribbon synapses. We show that mouse photoreceptors predominantly express RIM2 variants that lack the interaction domain for Munc13. Loss of full-length RIM2? in a RIM2? mutant mouse only marginally perturbs photoreceptor synaptic transmission. Our findings therefore strongly argue for a priming mechanism at the photoreceptor ribbon synapse that is independent of the formation of a RIM-Munc13-RAB3A complex and thus provide further evidence for a fundamental difference between photoreceptor ribbon synapses and conventional chemical synapses in synaptic vesicle exocytosis.SIGNIFICANCE STATEMENT RAB3A-interacting molecules 1 and 2 (RIM1/2) are essential regulators of exocytosis. At conventional chemical synapses, their function involves Ca(2+) channel clustering and synaptic vesicle priming and docking through interactions with Munc13 and RAB3A, respectively. Examining wild-type and RIM2 mutant mice, we show here that the sensory photoreceptor ribbon synapses most likely lack RIM1 and predominantly express RIM2 variants that lack the interaction domain for Munc13. Our findings demonstrate that the photoreceptor-specific RIM variants are not essential for synaptic vesicle priming at photoreceptor ribbon synapses, which represents a fundamental difference between photoreceptor ribbon synapses and conventional chemical synapses with respect to synaptic vesicle priming mechanisms.
EVALuna2:21339

Analysis of tetrodotoxin-sensitive sodium and low voltage-activated calcium channels in developing mouse retinal horizontal cells - Feigenspan, Andreas; Ohs, Alexandra; von Wittgenstein, Julia; Brandstätter, Johann Helmut; Babai, Norbert (Experimental Eye Research, 2020)
Expression patterns of voltage-gated ion channels determine the spatio-temporal dynamics of ion currents that supply excitable neurons in developing tissue with proper electrophysiological properties. The purpose of the study was to identify fast cationic inward currents in mouse retinal horizontal cells (HCs) and describe their biophysical properties at different developmental stages. We also aimed to reveal their physiological role in shaping light responses (LRs) in adult HCs. HCs were recorded in horizontal slices of wild-type mouse retina at postnatal stages ranging from p8 through p60. Voltage-dependent inward currents were isolated with appropriate voltage protocols and blockers specific for sodium and T-type calcium channels. LRs were evoked with full-field flashes (130 μW/cm2). Transient and steady inward currents were identified at all developmental stages. Transient currents were mediated by T-type calcium and TTX-sensitive sodium channels, whereas steady currents were blocked by cadmium, indicating the presence of high voltage-activated calcium channels. Activation and steady-state inactivation kinetics of T-type calcium channels revealed a contribution to the resting membrane potential during postnatal development. Additionally, both sodium and T-type calcium channels had an impact on HC LRs at light offset in adult animals. Our results showed that the voltage-dependent inward currents of postnatally developing mouse HCs consist of T-type calcium, TTX-sensitive sodium, and high voltage-activated calcium channels, and that transient ionic currents contributed to light-evoked responses of adult HCs, suggesting a role in HC information processing.
CRIS-Team Scopus Importer:2020-05-05
Keywords: Horizontal cells; Postnatal development; Retina; Sodium channels; T-type calcium channels

Angiotensin-Receptor-Associated Protein Modulates Ca2+ Signals in Photoreceptor and Mossy Fiber cells - Barro-Soria, Rene; Caicedo, Alejandro; Jaegle, Herbert; Merkel, Laura; Zhao, Na; Knop, Gabriel; Gierke, Kaspar; Dannullis, Andrea; Castrop, Hayo; Brandstätter, Johann Helmut; Kirchhoff, Frank; Feigenspan, Andreas; et al. (Scientific Reports, 2019)
Fast, precise and sustained neurotransmission requires graded Ca2+ signals at the presynaptic terminal. Neurotransmitter release depends on a complex interplay of Ca2+ fluxes and Ca2+ buffering in the presynaptic terminal that is not fully understood. Here, we show that the angiotensin-receptor-associated protein (ATRAP) localizes to synaptic terminals throughout the central nervous system. In the retinal photoreceptor synapse and the cerebellar mossy fiber-granule cell synapse, we find that ATRAP is involved in the generation of depolarization-evoked synaptic Ca2+ transients. Compared to wild type, Ca2+ imaging in acutely isolated preparations of the retina and the cerebellum from ATRAP knockout mice reveals a significant reduction of the sarcoendoplasmic reticulum (SR) Ca2+-ATPase (SERCA) activity. Thus, in addition to its conventional role in angiotensin signaling, ATRAP also modulates presynaptic Ca2+ signaling within the central nervous system.
CRIS-Team WoS Importer:2020-02-07

Cell types and synapses expressing the snare complex regulating proteins complexin 1 and complexin 2 in mammalian retina - Lux, Uwe; Ehrenberg, Johanna; Joachimsthaler, Anneka; Atorf, Jenny; Pircher, Bianca; Reim, Kerstin; Kremers, Jan; Gießl, Andreas; Brandstätter, Johann Helmut (International Journal of Molecular Sciences, 2021)
Complexins (Cplxs) 1 to 4 are components of the presynaptic compartment of chemical synapses where they regulate important steps in synaptic vesicle exocytosis. In the retina, all four Cplxs are present, and while we know a lot about Cplxs 3 and 4, little is known about Cplxs 1 and 2. Here, we performed in situ hybridization experiments and bioinformatics and exploited Cplx 1 and Cplx 2 single-knockout mice combined with immunocytochemistry and light microscopy to characterize in detail the cell type and synapse-specific distribution of Cplx 1 and Cplx 2. We found that Cplx 2 and not Cplx 1 is the main isoform expressed in normal and displaced amacrine cells and ganglion cells in mouse retinae and that amacrine cells seem to operate with a single Cplx isoform at their conventional chemical synapses. Surprising was the finding that retinal function, determined with electroretinographic recordings, was altered in Cplx 1 but not Cplx 2 single-knockout mice. In summary, the results provide an important basis for future studies on the function of Cplxs 1 and 2 in the processing of visual signals in the mammalian retina.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Amacrine cells; Complexin 1; Complexin 2; Conventional chemical synapses; Ganglion cells; Horizontal cells; Retina

DYNC2LI1 mutations broaden the clinical spectrum of dynein-2 defects - Keßler, Kristin; Wunderlich, Ina; Uebe, Steffen; Falk, Nathalie; Gießl, Andreas; Brandstätter, Johann Helmut; Popp, Bernt; Klinger, Patricia; Ekici, Arif Bülent; Sticht, Heinrich; Dörr, Helmuth-Günther; Reis, André; et al. (Scientific Reports, 2015)
Skeletal ciliopathies are a heterogeneous group of autosomal recessive osteochondrodysplasias caused by defects in formation, maintenance and function of the primary cilium. Mutations in the underlying genes affect the molecular motors, intraflagellar transport complexes (IFT), or the basal body. The more severe phenotypes are caused by defects of genes of the dynein-2 complex, where mutations in DYNC2H1, WDR34 and WDR60 have been identified. In a patient with a Jeune-like phenotype we performed exome sequencing and identified compound heterozygous missense and nonsense mutations in DYNC2LI1 segregating with the phenotype. DYNC2LI1 is ubiquitously expressed and interacts with DYNC2H1 to form the dynein-2 complex important for retrograde IFT. Using DYNC2LI1 siRNA knockdown in fibroblasts we identified a significantly reduced cilia length proposed to affect cilia function. In addition, depletion of DYNC2LI1 induced altered cilia morphology with broadened ciliary tips and accumulation of IFT-B complex proteins in accordance with retrograde IFT defects. Our results expand the clinical spectrum of ciliopathies caused by defects of the dynein-2 complex.
EVALuna2:9281

Electroretinographic Recordings in a Mouse Model for CSNB2 Featuring Mutations in the Cacna1f Gene - Atorf, Jenny; Specht, D.; Maw, M.; Brandstätter, Johann Helmut; Dieck, S. Tom; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2010)
Keywords: photoreceptors; electroretinography: non-clinical; synapse

Functional analyses of Pericentrin and Syne-2 interaction in ciliogenesis - Falk, Nathalie; Keßler, Kristin; Schramm, Sinja-Fee; Boldt, Karsten; Becirovic, Elvir; Michalakis, Stylianos; Regus-Leidig, Hanna; Noegel, Angelika A.; Ueffing, Marius; Thiel, Christian; Roepman, Ronald; Brandstätter, Johann Helmut; et al. (Journal of Cell Science, 2018)
Pericentrin (Pcnt) is a multifunctional scaffold protein and mutations in the human PCNT gene are associated with several diseases, including ciliopathies. Pcnt plays a crucial role in ciliary development in olfactory receptor neurons, but its function in the photoreceptor-connecting cilium is unknown. We downregulated Pcnt in the retina ex vivo and in vivo via a virus-based RNA interference approach to study Pcnt function in photoreceptors. ShRNA-mediated knockdown of Pcnt impaired the development of the connecting cilium and the outer segment of photoreceptors, and caused a nuclear migration defect. In protein interaction screens, we found that the outer nuclear membrane protein Syne-2 (also known as Nesprin-2) is an interaction partner of Pcnt in photoreceptors. Syne-2 is important for positioning murine photoreceptor cell nuclei and for centrosomal migration during early ciliogenesis. CRISPR/Cas9-mediated knockout of Syne-2 in cell culture led to an overexpression and mislocalization of Pcnt and to ciliogenesis defects. Our findings suggest that the Pcnt-Syne-2 complex is important for ciliogenesis and outer segment formation during retinal development and plays a role in nuclear migration.
EVALuna2:34620

Functional and Structural Development of Mouse Cone Photoreceptor Ribbon Synapses - Davison, Adam; Gierke, Kaspar; Brandstätter, Johann Helmut; Babai, Norbert (Investigative Ophthalmology & Visual Science, 2022)
PURPOSE. Cone photoreceptors of the retina use a sophisticated ribbon-containing synapse to convert light-dependent changes in membrane potential into release of synaptic vesicles (SVs). We aimed to study the functional and structural maturation of mouse cone photoreceptor ribbon synapses during postnatal development and to investigate the role of the synaptic ribbon in SV release. METHODS. We performed patch-clamp recordings from cone photoreceptors and their postsynaptic partners, the horizontal cells during postnatal retinal development to reveal the functional parameters of the synapses. To investigate the occurring structural changes, we applied immunocytochemistry and electron microscopy. RESULTS. We found that immature cone photoreceptor terminals were smaller, they had fewer active zones (AZs) and AZ-anchored synaptic ribbons, and they produced a smaller Ca2+ current than mature photoreceptors. The number of postsynaptic horizontal cell contacts to synaptic terminals increased with age. However, tonic and spontaneous SV release at synaptic terminals stayed similar during postnatal development. Multiquantal SV release was present in all age groups, but mature synapses produced larger multiquantal events than immature ones. Remarkably, at single AZs, tonic SV release was attenuated during maturation and showed an inverse relationship with the appearance of anchored synaptic ribbons. CONCLUSIONS. Our developmental study suggests that the presence of synaptic ribbons at the AZs attenuates tonic SV release and amplifies multiquantal SV release. However, spontaneous SV release may not depend on the presence of synaptic ribbons or voltage-sensitive Ca2+ channels at the AZs.
CRIS-Team Scopus Importer:2022-04-15
Keywords: cone photoreceptor; development; retina; ribbon synapse; synaptic vesicle release

Functional roles of complexin3 and complexin4 at mouse photoreceptor ribbon synapses - Babai, Norbert; Sendelbeck, Anna; Regus-Leidig, Hanna; Fuchs, Michaela; Mertins, Jasmin; Reim, Kerstin; Brose, Nils; Feigenspan, Andreas; Brandstätter, Johann Helmut (The Journal of Neuroscience, 2016)
Complexins (Cplxs) are SNARE complex regulators controlling the speed and Ca sensitivity of SNARE-mediated synaptic vesicle fusion. We have shown previously that photoreceptor ribbon synapses in mouse retina are equipped with Cplx3 and Cplx4 and that lack of both Cplxs perturbs photoreceptor ribbon synaptic function; however, Cplx3/4 function in photoreceptor synaptic transmission remained elusive. To investigate Cplx3/4 function in photoreceptor ribbon synapses, voltage-clamp recordings from postsynaptic horizontal cells were performed in horizontal slice preparations of Cplx3/4 wild-type (WT) and Cplx3/4 double knock-out (DKO) mice. We measured tonic activity in light and dark, current responses to changes in luminous intensity, and electrically evoked postsynaptic responses. Cplx3/4 decreased the frequency of tonic events and shifted their amplitude distribution to smaller values. Light responses were sustained in the presence of Cplx3/4, but transient in their absence. Finally, Cplx3/4 increased synaptic vesicle release evoked by electrical stimulation. Using electron microscopy, we quantified the number of synaptic vesicles at presynaptic ribbons after light or dark adaptation. In Cplx3/4 WT photoreceptors, the number of synaptic vesicles associated with the ribbon base close to the release site was significantly lower in light than in dark. This is in contrast to Cplx3/4 DKO photoreceptors, in which the number of ribbon-associated synaptic vesicles remained unchanged regardless of the adaptational state. Our results indicate a suppressing and a facilitating action of Cplx3/4 on Ca-dependent tonic and evoked neurotransmitter release, respectively, and a regulatory role in the adaptation-dependent availability of synaptic vesicles for release at photoreceptor ribbon synapses.

Genetic disruption of bassoon in two mutant mouse lines causes divergent retinal phenotypes - Ryl, Miriam; Urbasik, Alexander; Gierke, Kaspar; Babai, Norbert; Joachimsthaler, Anneka; Feigenspan, Andreas; Frischknecht, Renato; Stallwitz, Nina; Fejtová, Anna; Kremers, Jan; von Wittgenstein, Julia; Brandstätter, Johann Helmut (The FASEB Journal, 2021)
Bassoon (BSN) is a presynaptic cytomatrix protein ubiquitously present at chemical synapses of the central nervous system, where it regulates synaptic vesicle replenishment and organizes voltage-gated Ca2+ channels. In sensory photoreceptor synapses, BSN additionally plays a decisive role in anchoring the synaptic ribbon, a presynaptic organelle and functional extension of the active zone, to the presynaptic membrane. In this study, we functionally and structurally analyzed two mutant mouse lines with a genetic disruption of Bsn-Bsngt and Bsnko -using electrophysiology and high-resolution microscopy. In both Bsn mutant mouse lines, full-length BSN was abolished, and photoreceptor synaptic function was similarly impaired, yet synapse structure was more severely affected in Bsngt/gt than in Bsnko/ko photoreceptors. The synaptic defects in Bsngt/gt retina coincide with remodeling of the outer retina-rod bipolar and horizontal cell sprouting, formation of ectopic ribbon synaptic sites-and death of cone photoreceptors, processes that did not occur in Bsnko/ko retina. An analysis of Bsngt/ko hybrid mice revealed that the divergent retinal phenotypes of Bsngt/gt and Bsnko/ko mice can be attributed to the expression of the Bsngt allele, which triggers cone photoreceptor death and neurite sprouting in the outer retina. These findings shed new light on the existing Bsn mutant mouse models and might help to understand mechanisms that drive photoreceptor death.
CRIS-Team Scopus Importer:2021-04-16
Keywords: active zone; bassoon; photoreceptor; photoreceptor death; ribbon synapse

GlyT1 determines the glycinergic phenotype of amacrine cells in the mouse retina - Eulenburg, Volker; Knop, Gabriel; Sedmak, Tina; Schuster, Stefanie; Hauf, Katharina; Schneider, Julia; Feigenspan, Andreas; Joachimsthaler, Anneka; Brandstätter, Johann Helmut (Brain Structure & Function, 2018)
The amino acid glycine acts as a neurotransmitter at both inhibitory glycinergic and excitatory glutamatergic synapses predominantly in caudal regions of the central nervous system but also in frontal brain regions and the retina. After its presynaptic release and binding to postsynaptic receptors at caudal glycinergic synapses, two high-affinity glycine transporters GlyT1 and GlyT2 remove glycine from the extracellular space. Glycinergic neurons express GlyT2, which is essential for the presynaptic replenishment of the transmitter, while glial-expressed GlyT1 was shown to control the extracellular glycine concentration. Here we show that GlyT1 expressed by glycinergic amacrine cells of the retina does not only contribute to the control of the extracellular glycine concentration in the retina but is also essential for the maintenance of the glycinergic transmitter phenotype of this cell population. Specifically, loss of GlyT1 from the glycinergic AII amacrine cells impairs AII-mediated glycinergic neurotransmission and alters regulation of the extracellular glycine concentration, without changes in the overall distribution and/or size of glycinergic synapses. Taken together, our results suggest that GlyT1 expressed by amacrine cells in the retina combines functions covered by neuronal GlyT2 and glial GlyT1 at caudal glycinergic synapses.
EVALuna2:35241

Group I metabotropic glutamate receptors bind to protein phosphatase 1C: Mapping and modeling of interacting sequences. - Croci, Cristina; Sticht, Heinrich; Brandstätter, Johann Helmut; Enz, Ralf (Journal of Biological Chemistry, 2003)
The modulation of neurotransmitter receptors by kinases and phosphatases represents a key mechanism in controlling synaptic signal transduction. However, molecular determinants involved in the specific targeting and interactions of these enzymes are largely unknown. Here, we identified both catalytic γ-isoforms of protein phosphatase 1C (PP1γ1 and PP1γ2) as binding partners of the group I metabotropic glutamate receptors type 1a, 5a, and 5b in yeast cells and pull-down assays, using recombinant and native protein preparations. The tissue distribution of interacting proteins was compared, and protein phosphatase 1C was detected in dendrites of retinal bipolar cells expressing the respective interacting glutamate receptors. We mapped interacting domains within binding partners and identified five amino acids in the intracellular C termini of the metabotropic glutamate receptors type 1a, 5a, 5b, and 7b being both necessary and sufficient to bind protein phosphatase 1C. Furthermore, we show a dose-dependent competition of these C termini in binding the enzyme. Based on our data, we investigated the structure of the identified amino acids bound to protein phosphatase 1C by homology-based molecular modeling. In summary, these results provide a molecular description of the interaction between protein phosphatase 1C and metabotropic glutamate receptors and thereby increase our understanding of glutamatergic signal transduction.
UnivIS-Import:2015-04-14:Pub.2003.med.IB.profes_1.groupi

Heterogeneous presynaptic distribution of munc13 isoforms at retinal synapses and identification of an unconventional bipolar cell type with dual expression of munc13 isoforms: A study using munc13-exfp knock-in mice - Gierke, Kaspar; von Wittgenstein, Julia; Hemmerlein, Maike; Atorf, Jenny; Joachimsthaler, Anneka; Kremers, Jan; Cooper, Benjamin H.; Varoqueaux, Frederique; Regus-Leidig, Hanna; Brandstätter, Johann Helmut (International Journal of Molecular Sciences, 2020)
Munc13 isoforms are constituents of the presynaptic compartment of chemical synapses, where they govern important steps in preparing synaptic vesicles for exocytosis. The role of Munc13-1,-2 and-3 is well documented in brain neurons, but less is known about their function and distribution among the neurons of the retina and their conventional and ribbon-type chemical synapses. Here, we examined the retinae of Munc13-1-,-2-, and-3-EXFP knock-in (KI) mice with a combination of immunocytochemistry, physiology, and electron microscopy. We show that knock-in of Munc13-EXFP fusion proteins did not affect overall retinal anatomy or synapse structure, but slightly affected synaptic transmission. By labeling Munc13-EXFP KI retinae with specific antibodies against Munc13-1,-2 and-3, we found that unlike in the brain, most retinal synapses seem to operate with a single Munc13 isoform. A surprising exception to this rule was type 6 ON bipolar cells, which expressed two Munc13 isoforms in their synaptic terminals, ubMunc13-2 and Munc13-3. The results of this study provide an important basis for future studies on the contribution of Munc13 isoforms in visual signal processing in the mammalian retina.
CRIS-Team Scopus Importer:2020-11-06
Keywords: BrMunc13-2; Conventional synapse; Munc13-1; Munc13-3; Retina; Ribbon synapse; Type 6 ON bipolar cell; UbMunc13-2

Identification and characterisation of Simiate, a novel protein linked to the fragile X syndrome - Derlig, Kristin; Gießl, Andreas; Brandstätter, Johann Helmut; Enz, Ralf; Dahlhaus, Regina (PLoS ONE, 2013)
A strict regulation of protein expression during developmental stages and in response to environmental signals is essential to every cell and organism. Recent research has shown that the mammalian brain is particularly sensitive to alterations in expression patterns of specific proteins and cognitive deficits as well as autistic behaviours have been linked to dysregulated protein expression. An intellectual disability characterised by changes in the expression of a variety of proteins is the fragile X syndrome. Due to the loss of a single mRNA binding protein, the Fragile X Mental Retardation Protein FMRP, vast misregulation of the mRNA metabolism is taking place in the disease. Here, we present the identification and characterisation of a novel protein named Simiate, whose mRNA contains several FMRP recognition motifs and associates with FMRP upon co-precipitation. Sequence analysis revealed that the protein evolved app. 1.7 billion years ago when eukaryotes developed. Applying antibodies generated against Simiate, the protein is detected in a variety of tissues, including the mammalian brain. On the subcellular level, Simiate localises to somata and nuclear speckles. We show that Simiate and nuclear speckles experience specific alterations in FMR1(-/-) mice. An antibody-based block of endogenous Simiate revealed that the protein is essential for cell survival. These findings suggest not only an important role for Simiate in gene transcription and/or RNA splicing, but also provide evidence for a function of nuclear speckles in the fragile X syndrome. Indeed, transcription and splicing are two fundamental mechanisms to control protein expression, that underlie not only synaptic plasticity and memory formation, but are also affected in several diseases associated with mental disabilities.
EVALuna2:4700

Identification and immunocytochemical characterization of Piccolino, a novel Piccolo splice variant selectively expressed at sensory ribbon synapses of the eye and ear - Regus-Leidig, Hanna; Ott, Corinna; Löhner, Martina; Atorf, Jenny; Fuchs, Michaela; Sedmak, Tina; Kremers, Jan; Fejtova, Anna; Gundelfinger, Eckart D.; Brandstätter, Johann Helmut (PLoS ONE, 2013)
Piccolo is one of the largest cytomatrix proteins present at active zones of chemical synapses, where it is suggested to play a role in recruiting and integrating molecules relevant for both synaptic vesicle exo- and endocytosis. Here we examined the retina of a Piccolo-mutant mouse with a targeted deletion of exon 14 in the Pclo gene. Piccolo deficiency resulted in its profound loss at conventional chemical amacrine cell synapses but retinal ribbon synapses were structurally and functionally unaffected. This led to the identification of a shorter, ribbon-specific Piccolo variant, Piccolino, present in retinal photoreceptor cells, bipolar cells, as well as in inner hair cells of the inner ear. By RT-PCR analysis and the generation of a Piccolino-specific antibody we show that non-splicing of intron 5/6 leads to premature translation termination and generation of the C-terminally truncated protein specifically expressed at active zones of ribbon synapse containing cell types. With in situ proximity ligation assays we provide evidence that this truncation leads to the absence of interaction sites for Bassoon, Munc13, and presumably also ELKS/CAST, RIM2, and the L-type Ca(2) (+) channel which exist in the full-length Piccolo at active zones of conventional chemical synapses. The putative lack of interactions with proteins of the active zone suggests a function of Piccolino at ribbon synapses of sensory neurons different from Piccolo's function at conventional chemical synapses.
EVALuna2:21139

Lack of a Retinal Phenotype in a Syne-2/Nesprin-2 Knockout Mouse Model - Falk, Nathalie; Joachimsthaler, Anneka; Keßler, Kristin; Lux, Uwe; Noegel, Angelika Anna; Kremers, Jan; Brandstätter, Johann Helmut; Gießl, Andreas (Cells, 2019)
Syne-2 (also known as Nesprin-2) is a member of a family of proteins that are found primarily in the outer nuclear membrane, as well as other subcellular compartments. Syne-2 contains a C-terminal KASH transmembrane domain and is part of a protein network that associates the nuclear envelope to the cytoskeleton via the binding to actin filaments. Syne-2 plays a role in nuclear migration, nuclear positioning during retinal development, and in ciliogenesis. In a previous study, we showed a connection between Syne-2 and the multifunctional scaffold protein Pericentrin (Pcnt). The elimination of the interaction of Syne-2 and Pcnt showed defects in nuclear migration and the formation of outer segments during retinal development, as well as disturbances in centrosomal migration at the beginning of ciliogenesis in general. In this study, the Syne-2 KO mouse model Nesprin-2oABD (Syne-2(tm1Ngl), MGI) with special attention to Pcnt and ciliogenesis was analyzed. We show reduced expression of Syne-2 in the retina of the Syne-2 KO mouse but found no significant structural-and only a minor functional-phenotype. For the first time, detailed expression analyses showed an expression of a Syne-2 protein larger than 400 kDa (similar to 750 kDa) in the Syne-2/Nesprin-2 KO mouse. In conclusion, the lack of an overt phenotype in Syne-2/Nesprin-2 KO mice suggests the usage of alternative translational start sites, producing Syne-2 splice variants with an intact Pcnt interaction site. Nevertheless, deletion of the actin-binding site in the Syne-2/Nesprin-2 KO mouse revealed a high variability in scotopic oscillatory potentials assuming a novel function of Syne-2 in synchronizing inner retinal processes.
CRIS-Team WoS Importer:2019-11-29

Light-dependent regulation of neurotransmitter release from rod photoreceptor ribbon synapses involves an interplay of Complexin 4 and Transducin with the SNARE complex - Lux, Uwe; Meyer, Jutta; Jahn, Olaf; Davison, Adam; Babai, Norbert; Gießl, Andreas; Wartenberg, Anna; Sticht, Heinrich; Brose, Nils; Reim, Kerstin; Brandstätter, Johann Helmut (Frontiers in Molecular Neuroscience, 2024)
Adaptation of photoreceptor sensitivity to varying light intensities is a fundamental requirement for retinal function and vision. Adaptive mechanisms in signal transduction are well described, but little is known about the mechanisms that adapt the photoreceptor synapse to changing light intensities. The SNARE complex regulators Complexin 3 and Complexin 4 have been proposed to be involved in synaptic light adaptation by limiting synaptic vesicle recruitment and fusion. How this Complexin effect is exerted is unknown. Focusing on rod photoreceptors, we established Complexin 4 as the predominant Complexin in the light-dependent regulation of neurotransmitter release. The number of readily releasable synaptic vesicles is significantly smaller in light than in dark at wildtype compared to Complexin 4 deficient rod photoreceptor ribbon synapses. Electrophysiology indicates that Complexin 4 reduces or clamps Ca2+-dependent sustained synaptic vesicle release, thereby enhancing light signaling at the synapse. Complexin 4 deficiency increased synaptic vesicle release and desensitized light signaling. In a quantitative proteomic screen, we identified Transducin as an interactor of the Complexin 4-SNARE complex. Our results provide evidence for a presynaptic interplay of both Complexin 4 and Transducin with the SNARE complex, an interplay that may facilitate the adaptation of synaptic transmission to light at rod photoreceptor ribbon synapses.
CRIS-Team Scopus Importer:2024-04-05
Keywords: G protein; light adaptation; mouse retina; neurotransmitter release; ribbon synapses; rod photoreceptor

Photoreceptor degeneration in two mouse models for congenital stationary night blindness type 2 - Regus-Leidig, Hanna; Atorf, Jenny; Feigenspan, Andreas; Kremers, Jan; Maw, Marion A.; Brandstätter, Johann Helmut (PLoS ONE, 2014)
Light-dependent conductance changes of voltage-gated Cav1.4 channels regulate neurotransmitter release at photoreceptor ribbon synapses. Mutations in the human CACNA1F gene encoding the ?1F subunit of Cav1.4 channels cause an incomplete form of X-linked congenital stationary night blindness (CSNB2). Many CACNA1F mutations are loss-of-function mutations resulting in non-functional Cav1.4 channels, but some mutations alter the channels' gating properties and, presumably, disturb Ca(2+) influx at photoreceptor ribbon synapses. Notably, a CACNA1F mutation (I745T) was identified in a family with an uncommonly severe CSNB2-like phenotype, and, when expressed in a heterologous system, the mutation was shown to shift the voltage-dependence of channel activation, representing a gain-of-function. To gain insight into the pathomechanism that could explain the severity of this disorder, we generated a mouse model with the corresponding mutation in the murine Cacna1f gene (I756T) and compared it with a mouse model carrying a loss-of-function mutation (?Ex14-17) in a longitudinal study up to eight months of age. In ?Ex14-17 mutants, the b-wave in the electroretinogram was absent, photoreceptor ribbon synapses were abnormal, and Ca(2+) responses to depolarization of photoreceptor terminals were undetectable. In contrast, I756T mutants had a reduced scotopic b-wave, some intact rod ribbon synapses, and a strong, though abnormal, Ca(2+) response to depolarization. Both mutants showed a progressive photoreceptor loss, but degeneration was more severe and significantly enhanced in the I756T mutants compared to the ?Ex14-17 mutants.
EVALuna2:21185

PNUTS forms a trimeric protein complex with GABAC receptors and protein phosphatase 1. - Rose, Melanie; Dütting, Eva; Schröder, Nadja; Sticht, Heinrich; Brandstätter, Johann Helmut; Enz, Ralf (Molecular and Cellular Neuroscience, 2008)
Phosphorylation and dephosphorylation of neurotransmitter receptors represent an important mechanism to regulate synaptic signal transduction. Here, we identified PNUTS, a targeting subunit of protein phosphatase 1 (PP1) as a new binding partner of GABAC receptors. In the mammalian retina, PNUTS is co-expressed with GABAC receptors and PP1 in bipolar cells. PNUTS and PP1 were detected in membrane protein preparations of the retina and precipitate with GABAC receptor specific antibodies. Furthermore, PNUTS shuttles from the nucleus to the membrane in cells co-expressing GABAC receptors. We show simultaneous binding of PP1 and GABAC receptors to different domains of PNUTS, demonstrating that PNUTS cross-links PP1 and GABAC receptors. Finally, modeling studies showed that the PP1 docking motif of PNUTS fits into the binding pocket on the enzyme surface, despite a C-terminal adjacent proline. We suggest that PNUTS targets PP1 to synaptic sites, acting as a temporary bridge between the phosphatase and GABAC receptors. © 2007 Elsevier Inc. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2008.med.IB.profes_1.pnutsf_1
Keywords: Docking motif; GABA receptor; PP1C; Protein interaction; Retina; rho subunit

Rod photoreceptor ribbon synapses in DBA/2J mice show progressive age-related structural changes. - Fuchs, Michaela; Scholz, Michael; Sendelbeck, Anna; Atorf, Jenny; Schlegel, Christine Julie; Enz, Ralf; Brandstätter, Johann Helmut (PLoS ONE, 2012)
The DBA/2J mouse is a commonly used animal model in glaucoma research. The eyes of DBA/2J mice show severe age-related changes that finally lead to the degeneration of retinal ganglion cells and the optic nerve. Recent electroretinogram studies identified functional deficits, which suggest that also photoreceptor cells are involved in the pathological processes occurring in the DBA/2J mouse retina. In a comparative study, we examined anatomical and molecular changes in the retinae of DBA/2J and C57BL/6 control mice with light and electron microscopy and with PCR analyses. In the retina of the DBA/2J mouse, we found a thinning of the outer plexiform layer, the first synaptic layer in the transfer of visual signals, and age-dependent and progressive degenerative structural changes at rod photoreceptor ribbon synapses. The structural ribbon changes represent a photoreceptor synaptic phenotype that has not yet been described in this animal model of secondary angle-closure glaucoma. Furthermore, genes of the classical complement cascade were upregulated in the photoreceptor cells of aging DBA/2J mice, suggesting a putative link between ribbon synapse degradation and the innate immune system. © 2012 Fuchs et al.
UnivIS-Import:2015-04-14:Pub.2012.med.IB.profes_1.rodpho

Signal transmission at invaginating cone photoreceptor synaptic contacts following deletion of the presynaptic cytomatrix protein Bassoon in mouse retina - Babai, Norbert; Gierke, Kaspar; Müller, Tanja; Regus-Leidig, Hanna; Brandstätter, Johann Helmut; Feigenspan, Andreas (Acta Physiologica, 2019)
Aim: A key feature of the mammalian retina is the segregation of visual information in parallel pathways, starting at the photoreceptor terminals. Cone photoreceptors establish synaptic contacts with On bipolar and horizontal cells at invaginating, ribbon-containing synaptic sites, whereas Off bipolar cells form flat, non-ribbon-containing contacts. The cytomatrix protein Bassoon anchors ribbons at the active zone, and its absence induces detachment of ribbons from the active zone. In this study we investigate the impact of a missing Bassoon on synaptic transmission at the first synapse of the visual system. Methods: Release properties of cone photoreceptors were studied in wild-type and mutant mouse retinae with a genetic disruption of the presynaptic cytomatrix protein Bassoon using whole-cell voltage-clamp recordings. Light and electron microscopy revealed the distribution of Ca2+ channels and synaptic vesicles, respectively, in both mouse lines. Results: Whole-cell recordings from postsynaptic horizontal cells of the two mouse lines showed that the presence of Bassoon (and a ribbon) enhanced the rate of exocytosis during tonic and evoked release by increasing synaptic vesicle pool size and replenishment rate, while at the same time slowing synaptic vesicle release. Furthermore, the number of Cav1.4 channels and synaptic vesicles was significantly higher at wild-type than at Bassoon mutant synaptic sites. Conclusion: The results of our study demonstrate that glutamate release from cone photoreceptor terminals can occur independent of a synaptic ribbon, but seems restricted to active zones, and they show the importance of a the synaptic ribbon in sustained and spatially and temporally synchronized neurotransmitter release.
CRIS-Team Scopus Importer:2019-05-14
Keywords: Bassoon; cone photoreceptor; horizontal cell; retina; ribbon synapse; signal transmission

Simiate and the focal adhesion kinase FAK1 cooperate in the regulation of dendritogenesis - Rama, Ramya; Derlig, Kristin; Vießmann, Nina; Gossmann, Roman; Oriold, Fabian; Gießl, Andreas; Brandstätter, Johann Helmut; Enz, Ralf; Dahlhaus, Regina (Scientific Reports, 2022)
Despite the crucial importance of dendritogenesis for the correct functioning of neurons, the molecular mechanisms underlying neuronal arborisation are still not well understood. Current models suggest that distinct parts and phases of dendritic development are regulated by the expression of distinct transcription factors, that are able to target the cytoskeleton. Two proteins recently implicated in dendritogenesis are the Focal Adhesion Kinase FAK1 and the Actin-binding protein Simiate. Using heterologous expression systems as well as mouse brain extracts in combination with coprecipitation assays, we show that Simiate is able to associate with FAK1. Differential centrifugation experiments further revealed the interaction to be present in cytosolic as well as nuclear fractions. Inside the nucleus though, Simiate preferentially binds to a FAK1 isoform of 80 kDa, which has previously been shown to regulate transcription factor activity. Investigating the function of both proteins in primary hippocampal cultures, we further found that FAK1 and Simiate have distinct roles in dendritogenesis: While FAK1 increases dendrite length and number, Simiate preferentially enhances growth and branching. However, if being confined to the nucleus, Simiate selectively triggers primary dendrite formation, enhancing transcription activity at the same time. Since the effect on primary dendrites is specifically re-normalized by a co-expression of FAK1 and Simiate in the nucleus, the data implies that the two proteins interact to counterbalance each other in order to control dendrite formation. Looking at the role of the cytosolic interaction of FAK1 and Simiate, we found that neurotrophin induced dendritogenesis causes a striking colocalisation of FAK1 and Simiate in dendritic growth cones, which is not present otherwise, thus suggesting that the cytosolic interaction stimulates growth cone mediated dendritogenesis in response to certain external signals. Taken together, the data show that FAK1 and Simiate exert several and distinct actions during the different phases of dendritogenesis and that these actions are related to their subcellular localisation and their interaction.
CRIS-Team Scopus Importer:2022-07-15

Simiate is an Actin binding protein involved in filopodia dynamics and arborization of neurons - Derlig, Kristin; Ehrhardt, Toni; Giessi, Andreas; Brandstätter, Johann Helmut; Enz, Ralf; Dahlhaus, Regina (Frontiers in Cellular Neuroscience, 2014)
The Actin cytoskeleton constitutes the functional base for a multitude of cellular processes extending from motility and migration to cell mechanics and morphogenesis. The latter is particularly important to neuronal cells since the accurate functioning of the brain crucially depends on the correct arborization of neurons, a process that requires the formation of several dozens to hundreds of dendritic branches. Recently, a model was proposed where different transcription factors are detailed to distinct facets and phases of dendritogenesis and exert their function by acting on the Actin cytoskeleton, however, the proteins involved as well as the underlying molecular mechanisms are largely unknown. Here, we demonstrate that Simiate, a protein previously indicated to activate transcription, directly associates with both, G- and F-Actin and in doing so, affects Actin polymerization and Actin turnover in living cells. Imaging studies illustrate that Simiate particularly influences filopodia dynamics and specifically increases the branching of proximal, but not distal dendrites of developing neurons. The data suggests that Simiate functions as a direct molecular link between transcription regulation on one side, and dendritogenesis on the other, wherein Simiate serves to coordinate the development of proximal and distal dendrites by acting on the Actin cytoskeleton of filopodia and on transcription regulation, hence supporting the novel model.
EVALuna2:4699

Special characteristics of the transcription and splicing machinery in photoreceptor cells of the mammalian retina - Derlig, Kristin; Gießl, Andreas; Brandstätter, Johann Helmut; Enz, Ralf; Dahlhaus, Regina (Cell and Tissue Research, 2015)
Chromatin organization and the management of transcription and splicing are fundamental to the correct functioning of every cell but, in particular, for highly active cells such as photoreceptors, the sensory neurons of the retina. Rod photoreceptor cells of nocturnal animals have recently been shown to have an inverted chromatin architecture compared with rod photoreceptor cells of diurnal animals. The heterochromatin is concentrated in the center of the nucleus, whereas the genetically active euchromatin is positioned close to the nuclear membrane. This unique chromatin architecture suggests that the transcription and splicing machinery is also subject to specific adaptations in these cells. Recently, we described the protein Simiate, which is enriched in nuclear speckles and seems to be involved in transcription and splicing processes. Here, we examine the distribution of Simiate and nuclear speckles in neurons of mouse retinae. In retinal neurons of the inner nuclear and ganglion cell layer, Simiate is concentrated in a clustered pattern in the nuclear interior, whereas in rod and cone photoreceptor cells, Simiate is present at the nuclear periphery. Further staining with markers for the transcription and splicing machinery has confirmed the localization of nuclear speckle components at the periphery. Comparing the distribution of nuclear speckles in retinae of the nocturnal mouse with the diurnal degu, we found no differences in the arrangement of the transcription and splicing machinery in their photoreceptor cells, thus suggesting that the organization of these machineries is not related to the animal's lifestyle but rather represents a general characteristic of photoreceptor organization and function.
EVALuna2:4722

Strain differences in illumination-dependent structural changes at mouse photoreceptor ribbon synapses - Fuchs, Michaela; Sendelbeck, Anna; Atorf, Jenny; Kremers, Jan; Brandstätter, Johann Helmut (Journal of Comparative Neurology, 2013)
Photoreceptor cells encode light signals over a wide range of intensities with graded changes in their membrane potential. At their highly specialized ribbon synapses they transmit the signals to the postsynaptic neurons by the tonic release of glutamate, which is continuously adjusted to changes in light intensity. Such a level of performance requires adaptive mechanisms, and it is suggested that illumination-dependent changes in ribbon shape and size are one of these adaptive processes. In this study we compared structural properties of synaptic ribbons under various illumination conditions between three mouse strains: the pigmented C57BL/6 and the two albino strains Balb/c and B6(Cg)-Tyr(c-2J) /J (coisogenic to C57BL/6). In addition, electroretinograms (ERGs) recorded in the same groups were compared. In the C57BL/6 mouse a change in illumination did not result in structural alterations of the synaptic ribbon. Similarly, in the B6(Cg)-Tyr(c-2J) /J mouse only minor structural changes were detected. In contrast, the state of adaptation had a large influence on the ribbon structure of the Balb/c mouse. The ERG recordings showed only small functional differences between C57BL/6 and B6(Cg)-Tyr(c-2J) /J mice, but the retinal function of Balb/c mice was strongly compromised. We conclude that illumination-dependent changes of photoreceptor ribbon structure differ between strains and thus cannot be regarded as a general mechanism for light adaptation.
EVALuna2:21087

Studying protein function and the role of altered protein expression by antibody interference and three-dimensional reconstructions - Derlig, Kristin; Gießl, Andreas; Brandstätter, Johann Helmut; Enz, Ralf; Dahlhaus, Regina (Journal of Visualized Experiments, 2016)
A strict management of protein expression is not only essential to every organism alive, but also an important strategy to investigate protein functions in cellular models. Therefore, recent research invented different tools to target protein expression in mammalian cell lines or even animal models, including RNA and antibody interference. While the first strategy has gathered much attention during the past two decades, peptides mediating a translocation of antibody cargos across cellular membranes and into cells, obtained much less interest. In this publication, we provide a detailed protocol how to utilize a peptide carrier named Chariot in human embryonic kidney cells as well as in primary hippocampal neurons to perform antibody interference experiments and further illustrate the application of three-dimensional reconstructions in analyzing protein function. Our findings suggest that Chariot is, probably due to its nuclear localization signal, particularly well-suited to target proteins residing in the soma and the nucleus. Remarkably, when applying Chariot to primary hippocampal cultures, the reagent turned out to be surprisingly well accepted by dissociated neurons.
EVALuna2:4743
Keywords: Active motif; Antibody interference; Bioengineering; Issue 110; Nuclear proteins; Primary hippocampal cultures; Protein expression; Three-dimensional reconstructions

Synaptic vesicle release during ribbon synapse formation of cone photoreceptors - Davison, Adam; Gierke, Kaspar; Brandstätter, Johann Helmut; Babai, Norbert (Frontiers in Cellular Neuroscience, 2022)
Mammalian cone photoreceptors enable through their sophisticated synapse the high-fidelity transfer of visual information to second-order neurons in the retina. The synapse contains a proteinaceous organelle, called the synaptic ribbon, which tethers synaptic vesicles (SVs) at the active zone (AZ) close to voltage-gated Ca2+ channels. However, the exact contribution of the synaptic ribbon to neurotransmission is not fully understood, yet. In mice, precursors to synaptic ribbons appear within photoreceptor terminals shortly after birth as free-floating spherical structures, which progressively elongate and then attach to the AZ during the following days. Here, we took advantage of the process of synaptic ribbon maturation to study their contribution to SV release. We performed whole-cell patch-clamp recordings from cone photoreceptors at three postnatal (P) development stages (P8–9, P12–13, >P30) and measured evoked SV release, SV replenishment rate, recovery from synaptic depression, domain organization of voltage-sensitive Ca2+ channels, and Ca2+-sensitivity of exocytosis. Additionally, we performed electron microscopy to determine the density of SVs at ribbon-free and ribbon-occupied AZs. Our results suggest that ribbon attachment does not organize the voltage-sensitive Ca2+ channels into nanodomains or control SV release probability. However, ribbon attachment increases SV density at the AZ, increases the pool size of readily releasable SVs available for evoked SV release, facilitates SV replenishment without changing the SV pool refilling time, and increases the Ca2+- sensitivity of glutamate release.
CRIS-Team Scopus Importer:2022-12-02
Keywords: calcium; cone photoreceptor; development; pool size; retina; ribbon synapse; synaptic vesicle release

The absence of functional bassoon at cone photoreceptor ribbon synapses affects signal transmission at Off cone bipolar cell contacts in mouse retina - Babai, Norbert; von Wittgenstein, Julia; Gierke, Kaspar; Brandstätter, Johann Helmut; Feigenspan, Andreas (Acta Physiologica, 2020)
Aim: Off cone bipolar cells of the mammalian retina connect to cone photoreceptor synaptic terminals via non-invaginating flat contacts at a considerable distance from the only established neurotransmitter release site so far, the synaptic ribbon. Diffusion from the ribbon synaptic active zone is considered the most likely mechanism for the neurotransmitter glutamate to reach postsynaptic receptors on the dendritic tips of Off cone bipolar cells. We used a mutant mouse with functionally impaired photoreceptor ribbon synapses to investigate the importance of intact ribbon synaptic active zones for signal transmission at Off cone bipolar cell contacts. Methods: Whole-cell patch-clamp recordings from Off cone bipolar cells in a horizontal slice preparation of wildtype (Bsnwt) and mutant (BsnΔEx4/5) mouse retina were applied to investigate signal transmission between cone photoreceptors and Off cone bipolar cells. The distribution of postsynaptic glutamate receptors in Off cone bipolar cell dendrites was studied using multiplex immunocytochemistry. Results: Tonic synaptic activity and evoked release were significantly reduced in mutant animals. Vesicle replenishment rates and the size of the readily releasable pool were likewise decreased. The precisely timed transient current response to light offset changed to a sustained response in the mutant, exemplified by random release events only loosely time-locked to the stimulus. The kainate receptor distribution in postsynaptic Off cone bipolar cell dendritic contacts in BsnΔEx4/5 mice was largely disturbed. Conclusion: Our results suggest a major role of functional ribbon synaptic active zones for signal transmission and postsynaptic glutamate receptor organization at flat Off cone bipolar cell contacts.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Bassoon; cone photoreceptor; Off cone bipolar cell; retina; ribbon synapse; signal transmission

The BEACH Protein LRBA Promotes the Localization of the Heterotrimeric G-protein Golf to Olfactory Cilia - Kurtenbach, Stefan; Gießl, Andreas; Stromberg, Siv; Kremers, Jan; Atorf, Jenny; Rasche, Sebastian; Neuhaus, Eva M.; Herve, Denis; Brandstätter, Johann Helmut; Asan, Esther; Hatt, Hanns; Kilimann, Manfred W. (Scientific Reports, 2017)
BEACH domain proteins are involved in membrane protein traffic and human diseases, but their molecular mechanisms are not understood. The BEACH protein LRBA has been implicated in immune response and cell proliferation, and human LRBA mutations cause severe immune deficiency. Here, we report a first functional and molecular phenotype outside the immune system of LRBA-knockout mice: compromised olfaction, manifesting in reduced electro-olfactogram response amplitude, impaired food-finding efficiency, and smaller olfactory bulbs. LRBA is prominently expressed in olfactory and vomeronasal chemosensory neurons of wild-type mice. Olfactory impairment in the LRBA-KO is explained by markedly reduced concentrations (20-40% of wild-type levels) of all three subunits ?olf, ?1 and ?13 of the olfactory heterotrimeric G-protein, Golf, in the sensory cilia of olfactory neurons. In contrast, cilia morphology and the concentrations of many other proteins of olfactory cilia are not or only slightly affected. LRBA is also highly expressed in photoreceptor cells, another cell type with a specialized sensory cilium and heterotrimeric G-protein-based signalling; however, visual function appeared unimpaired by the LRBA-KO. To our knowledge, this is the first observation that a BEACH protein is required for the efficient subcellular localization of a lipid-anchored protein, and of a ciliary protein.
EVALuna2:21341

The first synapse in vision in the aging mouse retina - Gierke, Kaspar; Lux, Uwe; Regus-Leidig, Hanna; Brandstätter, Johann Helmut (Frontiers in Cellular Neuroscience, 2023)
Vision is our primary sense, and maintaining it throughout our lifespan is crucial for our well-being. However, the retina, which initiates vision, suffers from an age-related, irreversible functional decline. What causes this functional decline, and how it might be treated, is still unclear. Synapses are the functional hub for signal transmission between neurons, and studies have shown that aging is widely associated with synaptic dysfunction. In this study, we examined the first synapse of the visual system – the rod and cone photoreceptor ribbon synapse – in the mouse retina using light and electron microscopy at 2–3 months, 1 year, and >2 years of age. We asked, whether age-related changes in key synaptic components might be a driver of synaptic dysfunction and ultimately age-related functional decline during normal aging. We found sprouting of horizontal and bipolar cells, formation of ectopic photoreceptor ribbon synapses, and a decrease in the number of rod photoreceptors and photoreceptor ribbon synapses in the aged retina. However, the majority of the photoreceptors did not show obvious changes in the structural components and protein composition of their ribbon synapses. Noteworthy is the increase in mitochondrial size in rod photoreceptor terminals in the aged retina.
CRIS-Team Scopus Importer:2023-12-01
Keywords: aging; ectopic synapses; mitochondrial alterations; photoreceptor degeneration; retina remodeling; ribbon synapse

The Photoreceptor Ribbon Synapse in the Absence of Piccolo: An RNAi Approach - Regus-Leidig, Hanna; Atorf, Jenny; Feigenspan, Andreas; Boye, S.; Chiodo, V.; Seigel, G. M.; Hauswirth, W. W.; Kremers, Jan; Brandstätter, Johann Helmut (Investigative Ophthalmology & Visual Science, 2010)
Keywords: photoreceptors; synapse

Translocation of Distinct Alpha Synuclein Species from the Nucleus to Neuronal Processes during Neuronal Differentiation - Pieger, Katharina; Schmitt, Verena; Gauer, Carina; Gießl, Nadja; Prots, Iryna; Winner, Beate; Winkler, Jürgen; Brandstätter, Johann Helmut; Xiang, Wei (Biomolecules, 2022)
Alpha synuclein (aSyn) and its aggregation are crucial for the neurodegeneration of Parkinson's disease (PD). aSyn was initially described in the nucleus and presynaptic nerve terminals. However, the biology of nuclear aSyn and the link of aSyn between subcellular compartments are less understood. Current knowledge suggests the existence of various aSyn species with distinct structural and biochemical properties. Here, we identified a C-terminal-targeting aSyn antibody (Nu-aSyn-C), which has a high immunoaffinity towards aSyn in the nucleus. Comparing the Nu-aSyn-C antibody to aSyn antibodies developed against phosphorylated or aggregated forms, we observed that nuclear aSyn differs from cytosolic aSyn by an increased phosphorylation and assembly level in proliferating cells. Employing Nu-aSyn-C, we characterized aSyn distribution during neuronal differentiation in midbrain dopaminergic neurons (mDANs) derived from human-induced pluripotent stem cells (hiPSCs) and Lund human mesencephalic cells, and in primary rat hippocampal neurons. We detected a specific translocation pattern of aSyn during neuronal differentiation from the nucleus to the soma and finally to neuronal processes. Interestingly, a remarkable shift of Nu-aSyn-C-positive species towards neurites was detected in hiPSC mDANs from a PD patient carrying aSyn gene duplication. Together, our results reveal distinct nuclear and cytosolic aSyn species that redistribute during neuronal differentiation-a process that is altered in PD-derived neurons.
CRIS-Team WoS Importer:2022-09-09

T-Type Ca2+ Channels Boost Neurotransmission in Mammalian Cone Photoreceptors - Davison, Adam; Lux, Uwe; Brandstätter, Johann Helmut; Babai, Norbert (The Journal of Neuroscience, 2022)
It is a commonly accepted view that light stimulation of mammalian photoreceptors causes a graded change in membrane potential instead of developing a spike. The presynaptic Ca2+ channels serve as a crucial link for the coding of membrane potential variations into neurotransmitter release. Cav1.4 L-type Ca2+ channels are expressed in photoreceptor terminals, but the complete pool of Ca2+ channels in cone photoreceptors appears to be more diverse. Here, we discovered, employing whole-cell patch-clamp recording from cone photoreceptor terminals in both sexes of mice, that their Ca2+ currents are composed of low- (T-type Ca2+ channels) and high- (L-type Ca2+ channels) voltage-activated components. Furthermore, Ca2+ channels exerted self-generated spike behavior in dark membrane potentials, and spikes were generated in response to light/dark transition. The application of fast and slow Ca2+ chelators revealed that T-type Ca2+ channels are located close to the release machinery. Furthermore, capacitance measurements indicated that they are involved in evoked vesicle release. Additionally, RT-PCR experiments showed the presence of Cav3.2 T-type Ca2+ channels in cone photoreceptors but not in rod photoreceptors. Altogether, we found several crucial functions of T-type Ca2+ channels, which increase the functional repertoire of cone photoreceptors. Namely, they extend cone photoreceptor light-responsive membrane potential range, amplify dark responses, generate spikes, increase intracellular Ca2+ levels, and boost synaptic transmission.SIGNIFICANCE STATEMENT Photoreceptors provide the first synapse for coding light information. The key elements in synaptic transmission are the voltage-sensitive Ca2+ channels. Here, we provide evidence that mouse cone photoreceptors express low-voltage-activated Cav3.2 T-type Ca2+ channels in addition to high-voltage-activated L-type Ca2+ channels. The presence of T-type Ca2+ channels in cone photoreceptors appears to extend their light-responsive membrane potential range, amplify dark response, generate spikes, increase intracellular Ca2+ levels, and boost synaptic transmission. By these functions, Cav3.2 T-type Ca2+ channels increase the functional repertoire of cone photoreceptors.
CRIS-Team Scopus Importer:2022-09-09
Keywords: calcium; Cav3.2; cone photoreceptors; exocytosis; spike

ZIP3, a New Splice Variant of the PKC-ζ-interacting Protein Family, Binds to GABAC Receptors, PKC-ζ, and Kvβ2 - Croci, Cristina; Brandstätter, Johann Helmut; Enz, Ralf (Journal of Biological Chemistry, 2003)
The correct targeting of modifying enzymes to ion channels and neurotransmitter receptors represents an important biological mechanism to control neuronal excitability. The recent cloning of protein kinase C-zeta interacting proteins (ZIP1, ZIP2) identified new scaffolds linking the atypical protein kinase PKC-ζ to target proteins. GABAC receptors are composed of three ρ subunits (ρ1-3) that are highly expressed in the retina, where they are clustered at synaptic terminals of bipolar cells. A yeast two-hybrid screen for the GABAC receptor ρ3 subunit identified ZIP3, a new C-terminal splice variant of the ZIP protein family. ZIP3 was ubiquitously expressed in non-neuronal and neuronal tissues, including the retina. The ρ3-binding region of ZIP3 contained a ZZ-zinc finger domain, which interacted with 10 amino acids conserved in ρ1-3 but not in GABAA receptors. Consistently, only ρ1-3 subunits bound to ZIP3. ZIP3 formed dimers with ZIP1-3 and interacted with PKC-ζ and the shaker-type potassium channel subunit Kvβ2. Different domains of ZIP3 interacted with PKC-ζ and the p3 subunit, and simultaneous assembly of ZIP3, PKC-ζ and ρ3 was demonstrated in vitro. Subcellular co-expression of ZIP3 binding partners in the retina supported the proposed protein interactions. Our results indicate the formation of a ternary postsynaptic complex containing PKC-ζ, ZIP3, and GABAC receptors.
UnivIS-Import:2015-04-14:Pub.2003.med.IB.profes_1.zip3an